Nano Online 2016
DOI: 10.1515/nano.11671_2015.2
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of Micro-Nano Structured Triboelectric Nanogenerator with High Electric Output

Abstract: In this article, a new method is used to fabricate a high-performance triboelectric nanogenerator (TENG), which is convenient and cost-effective. A polyformaldehyde (POM) film with novel structures is prepared through electrospinning and is combined with a polytetrafluoroethylene (PTFE) film to assemble micro-nano structured TENG. The short-circuit current (I s ) and open-circuit voltage (V o ) of the TENG are up to 0.4343 mA and 236.8 V, respectively, and no significant change is observed by applying differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…On the other hand, PVP nanofibers are selected as the other frictional mat due to their strong ability to donate electrons [34]. Furthermore, the rough and porous surfaces of the nanofibers extend the contact area between the frictional materials which results in an increment of the triboelectric effect [35]. The technique of electrospinning was used to prepare both layers of nanofibers due to its low cost, versatility and simplicity for the fabrication of nanofibers using a wide variety of triboelectric mats [36].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, PVP nanofibers are selected as the other frictional mat due to their strong ability to donate electrons [34]. Furthermore, the rough and porous surfaces of the nanofibers extend the contact area between the frictional materials which results in an increment of the triboelectric effect [35]. The technique of electrospinning was used to prepare both layers of nanofibers due to its low cost, versatility and simplicity for the fabrication of nanofibers using a wide variety of triboelectric mats [36].…”
Section: Introductionmentioning
confidence: 99%
“…This method was chosen because of its simplicity, versatility and low-cost. Furthermore, the rougher surface of the fibers produced via electrospinning increases the effective contact area improving the output performance of the triboelectric nanogenerator [38].…”
Section: Fabrication Of the Tengmentioning
confidence: 99%
“…Furthermore, the very rough surface of the fibers fabricated via electrospinning can be used to improve the performance of the triboelectric nanogenerators. Although some authors have reported triboelectric nanogenerators fabricated via electrospinning [38][39], it is important to highlight the advantages of this fabrication method and the simplicity of this process for preparation of triboelectric nanogenerators at large scale using a low-cost production technology.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the fabrication process of the sensor is very simple and does not require expensive materials or technologies, which makes the process cheap and easy to perform [27,28]. Moreover, the process can be easily upgraded for large-scale production, which suggests a promising method for fabrication of such sensors on an industrial scale using a low-cost technology.…”
Section: Fabrication Of the Sensormentioning
confidence: 99%